Bibliometric analysis on medical education during Covid-19 pandemic - Hod, Rafidah (Fakulti Perubatan dan Sains Kesihatan UPM, 2022)
Medical education encompasses vast topics related to teaching-learning, among medical students. Bibliometric analysis is a scientific method to review properties of academic publications using quantitative statistical techniques. Aim of this study is to provide a bibliometric analysis of scholarly publications specifically on medical education related topics during the COVID-19 pandemic. The relevant documents on medical education were obtained from the Scopus database. Database search performed on 20th March 2022 and analysed using Microsoft Excel 365, VOSviewer and Harzing’s Publish or Perish. A total of 1436 documents were retrieved from Scopus database, left with 782 documents after filtering. For the past 2 years, the total citations received are 4974, while 44% of the documents were never cited. The most productive journal is BMC Medical Education. Most cited article is entitled: Medical Student Education in the Time of COVID-19 published in 2020. Most frequently used author keyword is covid-19. Visualisation on citation analysis among countries reveal the strongest link by United States of America with other countries. The current study provides a bibliometric perspective on the available medical education related publications in addressing issues related to covid-19 that is useful to guide them in considering possible future studies.